Firm performance in dynamic environments: The role of operational slack and operational scope - Kovach, Jeremy J.; Hora, Manpreet; Manikas, Andrew; Patel, Pankaj C. (Journal of Operations Management, 2015)
AbstractThis study examines the effects of operational scope (breadth of product offering, extent of geographical diversification, and extent to which production processes can effectively meet varying demand) and operational slack (resources in excess of what is required to fulfill expected demand) on firm performance, contingent on two components of a firm's dynamic environment, unpredictability and instability. We collate quarterly data on 3857 publicly traded firms in 19 industries from the years 1991 to 2013 (representing 99,559 firm‐quarter observations). Using panel data analysis, we find that narrow product offerings, low geographical diversification, low levels of excess capacity, and low inventory slack are each positively associated with firm performance. More importantly though, we find that operational scope is associated with improved performance in unpredictable environments, whereas operational slack is associated with improved performance in unstable environments. These findings contribute to the research on operations strategy by identifying the industry‐specific environmental conditions under which operational slack and operational scope are associated with firm performance.